Genomic analysis of cardiac surgery-associated Mycobacterium chimaera infections in Italy - Ghodousi, Arash; Borroni, Emanuele; Peracchi, Marta; Palù, Giorgio; Fallico, Loredana; Rassu, Mario; Manfrin, Vinicio; Mantegani, Paola; Monzillo, Vincenzina; Manganelli, Riccardo; Tortoli, Enrico; Cirillo, Daniela Maria (PloS one, 2020)
One hundred and twenty-two Mycobacterium chimaera strains isolated in Italy from cardiac surgery-related patients, cardiac surgery-unrelated patients and from heater-cooler units, were submitted to whole-genome sequencing and to subsequent SNP analysis. All but one strains isolated from cardiac surgery-related patients belonged to Subgroup 1.1 (19/23) or Subgroup 1.8 (3/23). Only 28 out of 79 strains isolated from heater-cooler units belonged to groupings other than 1.1 and 1.8. The strains isolated from cardiac surgery-unrelated patients were instead distributed across the phylogenetic tree. Our data, the first on isolates from Italy, are in agreement with a recent large genomic study suggesting a common source, represented by strains belonging to Subgroups 1.1 and 1.8, of cardiac surgery-related Mycobacterium chimaera infections. The strains belonging to groupings other than 1.1 and 1.8 isolated from heather-cooler units evidently resulted from contaminations at hospital level and had no share in the Mycobacterium chimaera outbreak. One Mycobacterium chimaera strain investigated in this study proved distant from every previously known Mycobacterium chimaera Groups (1, 2, 3 and 4) and we propose to assign to a novel group, named "Group 5".